Revision of the American species of the genus Prionus Geoffroy, 1762 (Coleoptera, Cerambycidae, Prioninae, Prionini) - Santos-Silva, Antonio; Nearns, Eugenio H.; Swift, Ian P. (Zootaxa, 2016)
A revision of the American species of Prionus Geoffroy, 1762 is presented. Prionus (Neopolyarthron) Semenov, 1899 and Prionus (Antennalia) Casey, 1912 are synonymized with Prionus Geoffroy, 1762. Homaesthesis LeConte, 1873 is considered a true subgenus of Prionus. Prionus (Homaesthesis) rhodocerus Linsley, 1957 and Prionus (Homaesthesis) linsleyi Hovore, 1981 are synonymized with Prionus simplex (Casey, 1912). Prionus beauvoisi Lameere, 1915 and Prionus (Neopolyarthron) debilis Casey, 1924 are synonymized with P. imbricornis (Linnaeus, 1767). Prionus (Neopolyarthron) townsendi Casey, 1912 and Prionus (Neopolyarthron) curticollis Casey, 1912 are synonymized with Prionus mexicanus Bates, 1884. Prionus batesi Lameere, 1920 is synonymized with Prionus aztecus Casey, 1912. Prionus hintoni Linsley, 1935 is synonymized with Prionus flohri Bates, 1884. Prionus (Antennalia) fissicornis parviceps Casey, 1912 is excluded as the synonym of Prionus fissicornis Haldeman, 1846 and instead synonymized with P. imbricornis (Linnaeus, 1767). Prionus (Prionus) validiceps Casey, 1912 is excluded from the synonymy of P. pocularis Dalman, 1817, and synonymized with P. (P.) californicus Motschulsky, 1845. Prionus (Prionus) tumidus Casey, 1912 is excluded from the synonymy of P. heroicus Semenov, 1907, and synonymized with P. (P.) californicus. The lectotype female and the paralectotype male of Prionus (Prionus) tristis are excluded from the synonym of P. (P.) heroicus and transferred to the synonym of P. (P.) californicus; the paralectotype female of P. (P.) tristis is maintained in the synonymy of P. (P.) heroicus. Prionus (Prionus) fontinalis Casey, 1914 is excluded from the synonymy of P. (P.) heroicus and synonymized with P. (P.) californicus. Prionus simplex is formally excluded from the Cerambycidae fauna of Oklahoma, USA. Comments on the page, plate, and figure of publication of Cerambyx laticollis Drury, 1773 are presented. Prionus (Trichoprionus) Fragoso & Monné, 1982 is considered a genus different from Prionus. Hypoprionus is designated as a replacement name for Prionellus Casey, 1924 and Cerambyx laticollis Drury, 1773 is designated as the type species. Comments on the type localities of Prionus emarginatus, Prionus palparis Say, 1824, and Prionus (Neopolyarthron) aztecus Casey, 1912 are presented. Prionus (Homaesthesis) integer sensu Linsley (1962) and Chemsak (1996) is described as P. (H.) geminus, new species. Comments on the date of publication of Prionus fissicornis Haldeman, 1846 are presented. Comments on the status of the syntypes of Cerambyx imbricornis Linnaeus, 1767 are also presented. Lectotype specimens for Prionus flohri Bates, 1884, Prionus (Prionus) tristis, and Prionus lecontei Lameere, 1912 are designated. Comments on the number of specimens used in the original description of Prionus californicus are presented, and a lectotype for this species is designated. New state records are presented for Prionus emarginatus Say, 1824; P. imbricornis (Linnaeus, 1767); P. aztecus Casey, 1912; P. poultoni Lameere, 1912; P. pocularis Dalman, 1817; and P. mexicanus Bates, 1884.